'Are you scared of being Muslim?' 100% Arabica and the influence of raï music in defining Beur communities in France. (1st December 2019) - Narcis, Stéphane
AbstractRaï music has evolved significantly over the last few decades, gaining an increasingly popular following in France. This music genre was prominently featured in Mahmoud Zammouri's film, 100% Arabica (1997). Previous analyses of raï music have suggested that this genre symbolizes Algerians' identity and their cultural tendency towards cynicism. This article attempts to refine that conclusion. Relationships between the characters of this film, the treatments of their gender roles and the depiction of their relationships to Islamic practices and cultural identity are all examined through the lens of anthropological diffusionism and social conflict. The results imply that when raï music is used as a Muslim cultural activity, this genre empowers and shapes identity among the Beur communities in France. However, the results also reveal how raï music facilitates cultural expression that can corrupt many of the core values held by Islam.